2023
DOI: 10.1021/acs.jafc.3c00453
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Prothioconazole Photodegradation in Aqueous Solution

Abstract: This study investigated the effects of light source, pH value, and NO3 – concentration on the photodegradation of prothioconazole in aqueous solution. The half-life (t 1/2) of prothioconazole was 173.29, 21.66, and 11.18 min under xenon, ultraviolet, and high-pressure mercury lamps, respectively. At pH values of 4.0, 7.0, and 9.0 under a xenon lamp light source, the t 1/2 values were 693.15, 231.05, and 99.02 min, respectively. Inorganic substance NO3 – clearly promoted the photodegradation of prothioconazole,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Many studies have demonstrated the influence of light energy on the photostability of various active pharmaceutical substances (APIs) and finished pharmaceutical products [ 11 , 12 ]. Also, the mechanisms of photodegradation of many APIs are known [ 13 , 14 ]. However, scarce data show the effect of particular spectral ranges of radiation on pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the influence of light energy on the photostability of various active pharmaceutical substances (APIs) and finished pharmaceutical products [ 11 , 12 ]. Also, the mechanisms of photodegradation of many APIs are known [ 13 , 14 ]. However, scarce data show the effect of particular spectral ranges of radiation on pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%